Facoemulsificação por córnea clara no meridiano mais curvo - Gonçalves, Fernando Pistarini [UNESP]; Rodrigues, Antonio Carlos Lottelli [UNESP] (My University, 2007)
Purpose: To evaluate the effect of phacoemulsification through clear cornea incision in the steepest meridian (ISM), on the magnitude of preoperative keratometric astigmatism. To map the magnitude of surgically induced astigmatism (SIA) by clear cornea incision in the positions: nasal (N), temporal (T), superior temporal (ST) and inferior temporal (IT). Methods: A prospective keratometric study was performed in 48 eyes of 48 patients, submitted to phacoemulsification by incision in the steepest meridian. Keratometric measures were taken preoperatively and one month after surgery. Surgically induced astigmatism was determined by the rectangular coordinate by the modified ten-step method. Results: There were 21 right eyes and 27 left eyes submitted to surgery, 16 eyes being N, 4 eyes T, 22 eyes TS, and 6 eyes TI. The average preoperative and postoperative cylindrical ametropias were, respectively, 1.06 ± 0.65 D and 0.89 ± 0.80 D. We found a statistical difference regarding decrease in the preoperative keratometric astigmatism (p=0.016). The total average of the surgically induced astigmatism was 0.94 ± 0.56 D. In relation to the groups, surgically induced astigmatism was 1.06 ± 0.66 D in N, 0.87 ± 0.20 D in T, 0.95 ± 0.55 D in TS and 0.61 ± 0.25 D in TI. There was no statistical difference in the surgically induced astigmatism between these groups (p=0.426). Conclusion: The technique was shown to be effective in decreasing the preoperative keratometric astigmatism. The surgically induced astigmatism was 1.06 ± 0.66 D in N, 0.95 ± 0.55 D in TS, 0.61 ± 0.25 D in T and 0.87 ± 0.20 D in TI.
Phacoemulsification using clear cornea incision in steepest meridian
Keywords: Astigmatism; Cornea/surgery; Corneal topography; Keratoconus; Phacoemulsification; Postoperative complications; Preoperative care